“Platform Schooling” Through “Platform Tutoring”? Unpacking the Relationship Between FJP Trainings and Journalistic Skills - Papa, Venetia (My University, 2024)
Big tech companies are increasingly suggesting tools and trainings to journalists, extending their well-documented influence in journalism. The discussion around journalistic skills have persisted for over a century and still today this topic remains vital attracting significant scholarship. Therein, the platformization of journalism is seen as a major challenge within the field, with an impact on the foundations of journalism challenging journalistic skills and work processes in newsrooms. This study entangles, to understand through the lens of visual-text centric approach the ways FJP through its trainings and e-courses suggested to journalists are encouraging certain journalistic skills to emerge. After the selection of three journalist-oriented tools provided by FJP, I collected 124 trainings, and 28 self-paced courses offered by the tools in their website to unpack the suggested skills. Findings suggest that FJP trainings and e-courses are promoting a set of platform-centric skills, which are deeply intertwined with platform-specific algorithms and business models. This can be viewed as a form of platform schooling which, in addition to journalism schools and work environments, mediates understanding of what are and what are not successful skills when practicing journalism.
Keywords: journalism; affordances; platforms; social media